Penunjukan Wali Anak Berdasarkan Asas Audi Et Alteram Partem dan Asas Wali Anak Hanya Satu - Nathania Amadea; Fatmi Utarie Nasution; Sherly Ayuna Putri (SIGn Jurnal Hukum, 2022)
This study examines and analyzes the dispute resolution of appointing a legal guardian based on the audi et alteram partem principle and only one legal guardian principle. This research combines normative juridical and empirical research methods. The types and sources of data used in this research are primary and secondary data. The primary data were collected using direct interviews with an informant. While the secondary data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The data obtained in this research were then analyzed juridically qualitatively. The results show that implementing the dispute resolution of appointing a legal guardian through a lawsuit realizes the principle of audi et alteram partem. Furthermore, with the realization of the audi et alteram partem principle, it will also directly realize the principle of only one guardian or what is known as the principle of one and indivisible. Therefore, it is recommended that the Government make amendments to Government Regulation No. 29 of 2019. In this case, explicitly and regulated disputes over guardianship rights should be examined through the jurisdictio contentiosa mechanism. Thus, anyone has the right to apply as a legal guardian, as long as they meet the requirements, have closeness, and the Child’s willingness.